STRENGTHENING FAMILY RESILIENCE THROUGH SUSTAINABLE ECONOMIC DEVELOPMENT BASED ON RELIGIOUS MODERATION - Syufa'at; Enjen Zaenal Mutaqin; Angga Nugraha; Rifa Dhatut Diana; Dhiya Roiha Anah; Umi Qoniatul Mubarokah; Maulidha Tri Kurnia (Universitas Islam Tribakti (UIT) Lirboyo Kediri, 2025)
The aim of this service is to increase community awareness about family resilience, religious moderation and a sustainable economy, as well as empowering the community to develop local economic potential based on local wisdom. The method used is Asset Based Community Development (ABCD), which consists of five stages: Discovery, Dream, Design, Define, and Destiny. This approach focuses on utilizing the assets and potential of society, not on problems or shortcomings. The results of the service show a significant increase in community understanding about family resilience, religious moderation, and sustainable economics. The development of food processing MSMEs based on local potential, especially oyster mushrooms, has been successful. This activity succeeded in encouraging the formation of an entrepreneurial community based on local wisdom. Increasing production and sales of processed oyster mushroom products has achieved significant results. Intensive assistance via WhatsApp groups for one month helps strengthen understanding and application of religious moderation values in the MSME business context.